Milvexian, an orally bioavailable, small‐molecule, reversible, direct inhibitor of factor XIa: In vitro studies and in vivo evaluation in experimental thrombosis in rabbits. (24th November 2021) - Wong, Pancras C.; Crain, Earl J.; Bozarth, Jeffrey M.; Wu, Yiming; Dilger, Andrew K.; Wexler, Ruth R.; Ewing, William R.; Gordon, David; Luettgen, Joseph M.
Abstract: Background: Milvexian (BMS‐986177/JNJ‐70033093) is an orally bioavailable factor XIa (FXIa) inhibitor currently in phase 2 clinical trials. Objectives: To evaluate in vitro properties and in vivo characteristics of milvexian. Methods: In vitro properties of milvexian were evaluated with coagulation and enzyme assays, and in vivo profiles were characterized with rabbit models of electrolytic‐induced carotid arterial thrombosis and cuticle bleeding time (BT). Results: Milvexian is an active‐site, reversible inhibitor of human and rabbit FXIa (Ki 0.11 and 0.38 nM, respectively). Milvexian increased activated partial thromboplastin time (APTT) without changing prothrombin time and potently prolonged plasma APTT in humans and rabbits. Milvexian did not alter platelet aggregation to ADP, arachidonic acid, or collagen. Milvexian was evaluated for in vivo prevention and treatment of thrombosis. For prevention, milvexian 0.063 + 0.04, 0.25 + 0.17, and 1 + 0.67 mg/kg+mg/kg/h preserved 32 ± 6*, 54 ± 10*, and 76 ± 5%* of carotid blood flow (CBF) and reduced thrombus weight by 15 ± 10*, 45 ± 2*, and 70 ± 4%*, respectively (* p  < .05; n  = 6/dose). For treatment, thrombosis was initiated for 15 min and CBF decreased to 40% of control. Seventy‐five minutes after milvexian administration, CBF averaged 1 ± 0.3, 39 ± 10, and 66 ± 2%* in groups treated with vehicle and milvexian 0.25 + 0.17 and 1 + 0.67 mg/kg+mg/kg/h, respectively (* p  < .05 vs. vehicle; n  = 6/group). The combination of milvexian 1 + 0.67 mg/kg+mg/kg/h and aspirin 4 mg/kg/h intravenous did not increase BT versus aspirin monotherapy. Conclusions: Milvexian is an effective antithrombotic agent with limited impact on hemostasis, even when combined with aspirin in rabbits. This study supports inhibition of FXIa with milvexian as a promising antithrombotic therapy with a wide therapeutic window.